Advancements in managing gout - Films for the Humanities & Sciences (Firm); Films Media Group; Information Television Network (New York, N.Y. : Films Media Group, 2012)
"Gout is the most common inflammatory arthritis among men. It can cause painful, disabling episodes and also, if inadequately treated, chronic disability and documented loss in the quality of life. Inadequate treatment, unfortunately, is very common due to a poor understanding of both diagnosis and patients' needs. This episode of Healthy Body, Healthy Mind shows that much of the misunderstanding and the poor outcome that results can be addressed by educating both physicians and the public about effective treatments available for the condition."--Container.
Introduction (1:26) -- Gout: A Form of Arthritis (2:28) -- Gout Treatment Plan (1:36) -- Gout Treatment Partnership (1:37) -- Chronic Gout & Related Disorders (1:44) -- Variety of Gout Factors (1:36) -- Finding the Cause of Joint Pain (1:23) -- A Severe Case of Gout (2:12) -- Monitoring Diet (1:40) -- Women and Estrogen Protection (2:17) -- The Perfect Storm for Gout (2:04) -- New Therapies Developing (2:16) -- Developing New Habits (1:12) -- Credits: Advancements in Managing Gout (0:32) -- Introduction (1:26) -- Gout: A Form of Arthritis (2:28) -- Gout Treatment Plan (1:36) -- Gout Treatment Partnership (1:37) -- Chronic Gout & Related Disorders (1:44) -- Variety of Gout Factors (1:36) -- Finding the Cause of Joint Pain (1:23) -- A Severe Case of Gout (2:12) -- Monitoring Diet (1:40) -- Women and Estrogen Protection (2:17) -- The Perfect Storm for Gout (2:04) -- New Therapies Developing (2:16) -- Developing New Habits (1:12) -- Credits: Advancements in Managing Gout (0:32).
Films on Demand is distributed by Films Media Group for Films for the Humanities & Sciences, Cambridge Educational, Meridian Education, and Shopware.
DVD.
107999
Keywords: Gout; Therapeutics; Disease management; Videorecording; Educational films